A case report of a mucocele - Pulungan, Ica Yulianti (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Frontal sinus mucoceles can present with a multitude of symptoms including ophthalmic disturbances. In benign conditions, they tend to expand by eroding the surrounding bony walls that displace and destroy structures through pressure and bony resorption. It becomes inflamed and filled with pus (pyocele) or a combination of both (mucopyocele). Due to its expansile nature, mucocele is important for diagnosis. Frontal mucoceles are benign and curable. Early recognition and management are important, as they can cause local, orbital, or intracranial complications. The purpose of this paper is to report a case of mucocele and emphasize the importance of radiological imaging, especially CT-Scan and MRI, in supporting the diagnosis of frontal sinus mucocele, detecting invasive processes to surrounding tissues and their extension to the intraorbita/intracranial, planning before surgery/biopsy, and evaluating the results of therapy.